Gracillin Isolated from Reineckia carnea Induces Apoptosis of A549 Cells via the Mitochondrial Pathway - Yang J; Cao L; Li Y; Liu H; Zhang M; Ma H; Wang B; Yuan X; Liu Q (Dove Medical Press, 2021)
Jianqiong Yang,1,* Ling Cao,2,* Yamei Li,2,* Hai Liu,2,3,* Minhong Zhang,1 Huamou Ma,1 Biao Wang,1 Xiaoliang Yuan,4 Qian Liu5,6 1Department of Clinical Medicine Research Center, The First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 2College of Pharmacy, Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 3National Engineering Research Center for Modernization of Traditional Chinese Medicine - Hakka Medical Resources Branch, Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 4Department of Respiratory Medicine, The First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 5Key Laboratory of Prevention and Treatment of Cardiovascular and Cerebrovascular Diseases of Ministry of Education, Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China; 6Department of Pediatric Surgery, The First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qian LiuGannan Medical University, #1 Yixueyuan Road, Ganzhou, Jiangxi, People’s Republic of ChinaTel +86 797 8169666Fax +86 797 8169600Email liuqiangmu2017@126.comBackground: Reineckia carnea is commonly used to treat cough, pneumonia and other diseases in China. In our previous study, it was found that the ethanol extracts of Reineckia carnea have a strong inhibitory effect on the proliferation of human lung cancer A549 cells. Here, we isolated gracillin from ethanol extracts for the first time.Purpose: Clarify the antiproliferation effect of gracillin on A549 cells and further explore its mechanisms via the mitochondrial pathway.Methods: Gracillin was isolated and purified by silica gel, D-101 macroporous resin and preparative RP-HPLC, then identified by NMR and HR-MS. The inhibitory effects of gracillin on the proliferation of A549 cells were detected by the MTS method. Its mechanisms were further explored by flow cytometry and Western blot.Results: A steroid saponin, gracillin, was isolated and identified from Reineckia carnea for the first time. In a concentration-dependent and time-dependent manner, gracillin significantly inhibited the proliferation of A549 cells with an IC50 value at 2.54 μmol/L and induced morphological changes. The results of flow cytometry analysis showed that the apoptosis rate of A549 cells was significantly increased (p < 0.05), and the cells proportion was obviously arrested in S phase. The concentration of intracellular calcium was raised (p < 0.01), and the mitochondrial membrane potential was greatly decreased (p < 0.01). In addition, the expression levels of Bax, caspase-3, cleaved caspase-3, and cytochrome C were dramatically up-regulated while Bcl-2 was down-regulated (p < 0.05) in A549 cells.Conclusion: This study confirmed that gracillin has a significant antiproliferative effect on A549 cells. Gracillin could induce the apoptosis of A549 cells through the mitochondrial pathway, which might be associated with regulation of the concentration of intracellular calcium, the mitochondrial membrane potential and the expression levels of Bax, Bcl-2, caspase-3, cleaved caspase-3, and cytochrome C.Keywords: Reineckia carnea, gracillin, antiproliferative activity, A549 cells, apoptosis